Maintaining optimism and instilling hope: The work of academic integrity practitioners and scholars - Usick, Brandy (Canadian Perspectives on Academic Integrity, 2019)
We open the second volume of the journal with a reflection on the state of our world and campuses and the importance of our work as academic integrity practitioners and scholars. We announce the evolution of the journal to include both peer-reviewed research and practitioner articles.